What is the Predictive Power of Visual Mathematics Literacy Perception and Its Sub-dimensions for Geometry Success? - Ilhan, Aziz; Tutak, Tayfun; Celik, Halil Coskun (Ani Yayincilik, 2019)
Purpose: In this study, it was aimed to examine the relationship between the visual mathematics literacy perceptions and its sub-dimension for geometry success levels of prospective teachers. It was also aimed to examine to what extent visual mathematics literacy perception and its sub-dimensions predicted geometry success. Research Methods: This study was designed in accordance with a qualitative, scanning model. The research was carried out with 232 (97 males and 135 females) prospective teachers who studied in Mathematics Education Program at Firat University, Education Faculty, and were selected by simple random sampling method. Visual Mathematics Literacy Perception Scale and Geometry Success Literacy Perception Scale and Geometry Success Test were employed in this study as data collection tools. Correlation analysis and multiple regression analysis were used for analyzing the data. Findings: After the data were analyzed, it was determined that there was a positive relationship between the visual mathematics literacy perception and geometry success of prospective teachers. It was also determined that visual mathematics literacy perception is a meaningful predictor of geometry success. Implications for research and practice: Providing trainings on these concepts in the direction of the results, to investigate the concept of perception on other learning areas of mathematics and conducting experimental studies on the perception of visual mathematics literacy are suggested. (C) 2019 Ani Publishing Ltd. All rights reserved
Görsel Matematik Okuryazarlığı Alt Boyutlarının Geometri Başarısını Yordama Gücü Nedir?
Keywords: visual mathematics literacy; mathematics literacy; geometry success; mathematics education; teacher candidates